Associations between schistosomiasis and HIV‐1 acquisition risk in four prospective cohorts: a nested case‐control analysis. Issue 6 (25th June 2020) - Bochner, Aaron F; Baeten, Jared M; Secor, W Evan; van Dam, Govert J; Szpiro, Adam A; Njenga, Sammy M; Corstjens, Paul L A M; Newsam, Austin; Mugo, Nelly R; Celum, Connie; Mujugira, Andrew; McClelland, R Scott; et al.
Abstract: Introduction: Globally, schistosomes infect approximately 200 million people, with 90% of infections in sub‐Saharan Africa. Schistosomiasis is hypothesized to increase HIV‐1 acquisition risk, and multiple cross‐sectional studies reported strong associations. We evaluated this hypothesis within four large prospective cohorts. Methods: We conducted nested case‐control analyses within three longitudinal cohorts of heterosexual HIV‐1 serodiscordant couples and one female sex worker (FSW) cohort from Kenya and Uganda. The serodiscordant couples studies were conducted between 2004 and 2012 while the FSW cohort analysis included participant follow‐up from 1993 to 2014. Cases HIV‐1 seroconverted during prospective follow‐up; three controls were selected per case. The presence of circulating anodic antigen in archived serum, collected prior to HIV‐1 seroconversion, identified participants with active schistosomiasis; immunoblots determined the schistosome species. Data from serodiscordant couples cohorts were pooled, while the FSW cohort was analysed separately to permit appropriate confounder adjustment. Results: We included 245 HIV‐1 seroconverters and 713 controls from the serodiscordant couples cohorts and 330 HIV‐1 seroconverters and 962 controls from the FSW cohort. The prevalence of active schistosomiasis was 20% among serodiscordant couples and 22% among FSWs. We found no association between schistosomiasis and HIV‐1 acquisition risk among males (adjusted odds ratio (aOR) = 0.99, 95% CI 0.59 to 1.67) or females (aOR = 1.21, 95% CI 0.64 to 2.30) in serodiscordant couples. Similarly, in the FSW cohort we detected no association (adjusted incidence rate ratio (aIRR) = 1.11, 95% CI 0.83 to 1.50). Exploring schistosome species‐specific effects, there was no statistically significant association between HIV‐1 acquisition risk and Schistosoma mansoni (serodiscordant couples: aOR = 0.90, 95% CI 0.56 to 1.44; FSW: aIRR = 0.83, 95% CI 0.53 to 1.20) or Schistosoma haematobium (serodiscordant couples: aOR = 1.06, 95% CI 0.46 to 2.40; FSW: aIRR = 1.64, 95% CI 0.93 to 2.87) infection. Conclusions: Schistosomiasis was not a strong risk factor for HIV‐1 acquisition in these four prospective studies. S. mansoni was responsible for the majority of schistosomiasis in these cohorts, and our results do not support the hypothesis that S. mansoni infection is associated with increased HIV‐1 acquisition risk. S. haematobium infection was associated with a point estimate of elevated HIV‐1 risk in the FSW cohort that was not statistically significant, and there was no trend towards a positive association in the serodiscordant couples cohorts.